Translation, reliability and validity of the Greek functional mobility scale (FMS) for children with cerebral palsy. Issue 8 (10th April 2022) - Skoutelis, Vasileios C.; Dimitriadis, Zacharias; Kalamvoki, Efstratia; Vrettos, Stamatis; Kontogeorgakos, Vasileios; Dinopoulos, Argirios; Papagelopoulos, Panayiotis; Kanellopoulos, Anastasios
Abstract: Purpose: To translate and investigate the reliability and validity of the Greek version of the Functional Mobility Scale (FMS). Methods: FMS was translated into Greek. Test-retest reliability (Cohen's weighted kappa coefficient, κw ) and concurrent validity (Spearman's rank correlation coefficient, rs ) of the Greek version of FMS were assessed in children with Cerebral Palsy (CP). Sixty children (mean age 7.82 ± 3.20 years) were recruited. Physical therapists administered the FMS by interviewing parents about their children's mobility status. The Gross Motor Function Classification System (GMFCS) was additionally used for testing concurrent validity. Results: The translation of the FMS was deemed easy to understand and administer. The Greek FMS was demonstrated to have almost perfect test-retest reliability ( κw =0.98–1.00), and very strong correlation with the GMFCS (–0.85 ≤ rs ≤ −0.89, p < 0.001). Conclusions: The Greek version of the FMS was shown to be a reliable and valid classification system for CP and can be used with confidence by Greek physical therapists. Implications for rehabilitation: The FMS provides a very simple and practical outcome measure of functional mobility in children with CP. The use of the reliable and valid Greek FMS will enhance the physical therapy assessment process in the Greek population, by offering the feasibility to detect the motor performance changes in children with CP as they grow or following interventions. The current study renders the Greek FMS available for utilization by physical therapists in order to quantify the independent mobility in children with CP.